Personal Guidance Service to Enhance The Independence of Children with Multiple Disabilities with Visual Impairment - Dapa, Aldjon Nixon; Rustiani, Ni Kadek Diana (Angstrom Centre of Education, 2024)
This study aims to identify, analyze and interpret the process of providing personal guidance services carried out by classroom teachers to children with MDVI barriers at SLB A Bartemeus Manado. This research uses case study qualitative research methods. The subject in this study amounted to one person, and the sampling in this study was purposive sampling. The methods used in collecting this data are observation, interview, and documentation. The results showed that the subject experienced very significant changes after receiving personal guidance services, such as HP being able to walk alone, mastering Mobility Orientation in the orphanage and school environment, being able to cook, iron, wash clothes, wash dishes, be more confident and independent so that he does not feel afraid in carrying out his daily activities.